2018
DOI: 10.1186/s12859-018-2239-6
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the HLA typing performance of Polysolver and Optitype in 50 Danish parental trios

Abstract: BackgroundThe adaptive immune response intrinsically depends on hypervariable human leukocyte antigen (HLA) genes. Concomitantly, correct HLA phenotyping is crucial for successful donor-patient matching in organ transplantation. The cost and technical limitations of current laboratory techniques, together with advances in next-generation sequencing (NGS) methodologies, have increased the need for precise computational typing methods.ResultsWe tested two widespread HLA typing methods using high quality full gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 47 publications
(64 reference statements)
0
30
2
Order By: Relevance
“…In the Matey‐Hernandez et al . study, Polysolver and OptiType were benchmarked against 50 Danish parental trios . In this study, Polysolver was reported to be the most accurate typing tool at two‐field resolution, which is in discordance with the results obtained by Kiyotani et al .…”
Section: Introductioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In the Matey‐Hernandez et al . study, Polysolver and OptiType were benchmarked against 50 Danish parental trios . In this study, Polysolver was reported to be the most accurate typing tool at two‐field resolution, which is in discordance with the results obtained by Kiyotani et al .…”
Section: Introductioncontrasting
confidence: 53%
“…In the Matey-Hernandez et al study, Polysolver and OptiType were benchmarked against 50 Danish parental trios. 34 In this study, Polysolver was reported to be the most accurate typing tool at two-field resolution, which is in discordance with the results obtained by Kiyotani et al Another study, performed by Bauer et al, evaluated five computational tools for HLA typing: OptiType, PHLAT, HLA-VBSeq, seq2HLA, and HLAminer. 35 The performance of the five tools was benchmarked against a curated dataset of more than 1300 patient samples from five published studies where the patient samples had been HLA genotyped using PCR-based methods.…”
Section: Introductioncontrasting
confidence: 42%
See 1 more Smart Citation
“…genotyping tools has been carried out by multiple groups relying on either real-time PCR validation of a small set of HLA alleles 33 or correlations of HLA-types between family trios based on haplotype inferences. 34 We have established a novel approach for evaluating HLA genotyping methods, eliminating the uncertainty of haplotype inference and including all called HLA alleles. The details of our approach will be described in a separate manuscript (Ren Y. et al, in preparation), but as illustrated in Supplement Figure S2 using 12 TCGA cases, the performances of the current class-I and class-I HLA genotyping methods are vastly different, as represented by consistencies of the called HLA subtypes between germline (blood), tumor, and normal tissue exomes of the same patient.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted to compare the accuracy of different software [21][22][23][24]. Bauer et al…”
Section: Introductionmentioning
confidence: 99%